Finite elements analysis of the deformation applied to the 6061-T6 aluminum alloy by equal channel angular pressing (2019)
The severe plastic deformation process Equal Channel Angular Pressing (ECAP/ECAE), was simulated under the theory of finite elements using the software ANSYS, in search of different elastoplastic responses that can be presented to a sample of 6061-T6 aluminum alloy. Variations of the mechanical parameters of the ECAP matrix, such as its geometry (external angle (Ψ) and internal angle (Φ)) and the friction conditions of the process were studied. The influence of each of these parameters on the behavior of the material was analyzed. The results obtained were compared with the theoretical predictions that have been arranged throughout the ECAE / ECAP study by different researchers.